TBL vs. PBL: Which is More Effective Model in Economics Learning? - Yunikawati, Nur Anita; Tuanani, Mella Artha Mevia (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2022)
Economics subject discusses many economic problems in students’ circumstances, and it requires critical thinking ability. However, the ability of students to think critically linked to economics is still an insufficient category. Therefore, it needs to implement the learning model that affects the development of students’ critical thinking. This research aims to compare the effectiveness of team-based learning (TBL) and problem-based learning (PBL) models in economics learning as an attempt to enhance students’ critical thinking skills. This study adopted a quasi-experimental method using two experimental classes treated differently. The pre-test and post-test data obtained were used to estimate the research hypotheses through the ANCOVA test. The results of this study indicate differences in the improvement of critical thinking skills in TBL and PBL class students, with a significance level of 0.007 (<0.05). Students in the TBL class experienced increased critical thinking skills 10% superior to students in the PBL class. Therefore, TBL can be an alternative for teachers of economics or other relevant subjects to apply in teaching-learning activities by paying attention to the content rather than the material to be delivered. Further research regarding the TBL model with other 4Cs skills besides critical thinking is needed.